Optimization of Environmental, Occupational Safety and Health Management through Automatic Waterfill Innovation for Fuel Efficiency, Time Effectiveness, and Minimizing Potential for Hazardous and Toxic Waste Contamination in Coal Mining - Amirudin, Agus; Zulkarnaen, Zulkarnaen; Gunawan, Gunawan; Saptaputra, Syawal Kamiluddin; Lestari, Ida Ayu Indira Dwika (GLOBAL HEALTH SCIENCE GROUP, 2024)
The purpose of this study is to implement automatic waterfill innovation for fuel efficiency, time effectiveness, and minimizing the potential for hazardous and toxic waste contamination in coal mining. This research method is quantitative with a research and development approach. This research was conducted at PT. Antareja Mahada Makmur site Multi Harapan Utama. The research was conducted in June 2024. This research began with an analysis of the current conditions regarding the water truck process in the waterfill; setting targets with Specific, Measurable, Achievable, Relevant, and Time-Bound indicators. After the implementation of automatic waterfill, the operational time required to turn the waterfill on and off was drastically reduced because automation eliminates manual steps. It also significantly reduced the total waterfill running time per shift from 480 minutes to just 144 minutes, which means significant energy savings, increased time efficiency, and reduced fuel waste and potential damage due to excessive operations. The application of automatic waterfill in coal mines brings many benefits, including improved operational quality, cost savings, increased safety, and reduced environmental impact. In addition, this system also has a positive impact on operator motivation and job satisfaction.